The Influence of Brand Image and Product Quality on Purchase Decisions of Eiger Products in Surabaya - Sultan Syarif Cakrayuda; Maharani Ikaningtyas (International Journal of Social, Economic, and Business, 2025)
In today's competitive business world, companies need effective strategies to attract customers and keep them loyal. Two important factors that influence consumer purchasing decisions are brand image and product quality.This research explores how brand image and product quality affect the purchasing decisions of Eiger products in Surabaya. The study uses a quantitative approach with a survey method. The target population includes consumers who have bought Eiger products in Surabaya. A purposive sampling technique was used, involving 156 respondents. Data was collected through a questionnaire distributed via Google Forms.For data analysis, multiple linear regression was applied to examine the relationship between independent and dependent variables. The findings reveal that brand image has a positive and significant effect on consumer purchasing decisions. Likewise, product quality plays a crucial role in influencing purchasing choices. Overall, both brand image and product quality contribute significantly to shaping consumer decisions when purchasing Eiger products in Surabaya.